Expansão urbana e produção imobiliária na região sul de João Pessoa-PB - Oliveira, Matheus Henrique de Souza Genuino (2021)
The urban space is extremely diverse, but it becomes homogenized through the intervention of capital, especially the interests of those who own the means of production. The absorption of capital surplus currently takes place especially in urban space through the intervention of real estate. In this work, we intend to bring a discussion about investments in the real estate sector in the outskirts of João Pessoa, especially in what we call Region of Valentina which covers the neighborhood of Valentina Figueiredo and its surroundings, located in an expanding area of the city, the current South Zone Capital is like a web and in its accelerated process of accumulation has in the urban space its main form of materialization, urban expansion is then directly linked to the interests of capital. The paths through which urbanization passes are necessarily tiled (planned) by capitalism. In this text, we highlight João Pessoa's contemporary urbanization process. The central axis of the research is to think about the socio-spatial transformation in the Region of Valentina Figueiredo located on the outskirts of the urban area of João Pessoa. To analyze the displacement of investments in the housing issue aimed at a lower middle class population in peripheral areas of the city. This movement is given especially by the price of urban land moved by the real estate market and also valued by public policies and investments. Highlighting the contradiction between the center and the periphery, our question then is to understand why and from what moment real estate investments start to take place in the outskirts of the city as well. We will then reflect on the 'inclusion' of the periphery in the productive circuit of capital, especially linked to real estate. And, beyond that, changes in social perspectives, transformations strictly linked to the first trend, that is, to the new standards established by this real estate structure.